Pediatric emergency departments' readiness for change toward improving suicide prevention: A mixed‐methods study with US leaders. Issue 5 (25th October 2022) - Bowden, Cadence F.; Worsley, Diana; Esposito, Jeremy M.; Cutler, Gretchen J.; Doupnik, Stephanie K.
Abstract: Objective: To assess pediatric emergency departments' (PEDs) current suicide prevention practices and climate for change to improve suicide prevention for youth. Methods: We conducted an explanatory, sequential mixed‐methods study. First, we deployed a national, cross‐sectional survey of PED leaders identified through publicly available data in Fall 2020, and then we conducted follow‐up interviews with those who expressed interest. The survey queried each PED's suicide prevention practices and measured readiness for change to improve suicide prevention practices using questions scored on a 5‐point Likert scale. Interviews gathered further, in‐depth descriptions of PEDs' practices and culture. Interviews were audio‐recorded, transcribed verbatim, and analyzed using a rapid analysis approach. Results: Of 135 PED directors eligible to complete the survey, 64 responded (response rate 47%). A total of 64% of PEDs had a mental health specialist available 24 hours/day, 7 days/week; 80% reported practicing mental health disposition planning, and 41% reported practicing psychiatric medication management. Altogether 91% of directors agreed or strongly agreed that their PED had a positive culture and 92% agreed/strongly agreed that their PED was ready for change. However, 31% disagreed/strongly disagreed that their PED had tools for evaluation and quality measurement. Resources needed for change (including budget, staffing, training, and facilities) varied across institutions. Interviews with our convenience sample of 21 directors revealed varying suicide prevention practices and confirmed that standardization, evaluation, and quality improvement initiatives were needed at most institutions. Leaders reported a high interest in improving care. Conclusions: PED leaders reported high motivation to improve suicide prevention services for young people, and reported needing quality improvement infrastructure to monitor and guide improvement.